Improving TCR Gene Therapy for Treatment of Haematological Malignancies. (26th January 2012) - Nicholson, Emma; Ghorashian, Sara; Stauss, Hans
Abstract : Adoptive immunotherapy using TCR gene modified T cells may allow separation of beneficial Graft versus tumour responses from harmful GvHD. Improvements to this include methods to generate high avidity or high affinity TCR, improvements in vector design and reduction in mispairing. Following adoptive transfer, TCR transduced T cells must be able to survive and persist in vivo to give most effective antitumour responses. Central memory or naive T cells have both been shown to be more effective than effector cells at expanding and persisting in vivo. Lymphodepletion may enhance persistence of transferred T cell populations. TCR gene transfer can be used to redirect CD4 helper T cells, and these could be used in combination with CD8+ tumour specific T cells to provide help for the antitumour response. Antigen specific T regulatory T cells can also be generated by TCR gene transfer and could be used to suppress unwanted alloresponses.